Examining the Effects of External or Internal Radiation Exposure of Juvenile Mice on Late Morbidity after Infection with Influenza A - Misra, Ravi S. (Radiat Res, 2015)
A number of investigators have suggested that exposure to low-dose radiation may pose a potentially serious health risk. However, the majority of these studies have focused on the short-term rather than long-term effects of exposure to fixed source radiation, and few have examined the effects of internal contamination. Additionally, very few studies have focused on exposure in juveniles, when organs are still developing and could be more sensitive to the toxic effects of radiation. To specifically address whether early-life radiation injury may affect long-term immune competence, we studied 14-day-old juvenile pups that were either 5 Gy total-body irradiated or injected internally with 50 μCi soluble (137)Cs, then infected with influenza A virus at 26 weeks after exposure. After influenza infection, all groups demonstrated immediate weight loss. We found that externally irradiated, infected animals failed to recover weight relative to age-matched infected controls, but internally (137)Cs contaminated and infected animals had a weight recovery with a similar rate and degree as controls. Externally and internally irradiated mice demonstrated reduced levels of club cell secretory protein (CCSP) message in their lungs after influenza infection. The externally irradiated group did not recover CCSP expression even at the two-week time point after infection. Although the antibody response and viral titers did not appear to be affected by either radiation modality, there was a slight increase in monocyte chemo-attractant protein (MCP)-1 expression in the lungs of externally irradiated animals 14 days after influenza infection, with increased cellular infiltration present. Notably, an increase in the number of regulatory T cells was seen in the mediastinal lymph nodes of irradiated mice relative to uninfected mice. These data confirm the hypothesis that early-life irradiation may have long-term consequences on the immune system, leading to an altered antiviral response.